2018
DOI: 10.1371/journal.pone.0196976
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-targeted delivery of dexamethasone by anti-VCAM-1 SAINT-O-Somes in mouse endotoxemia

Abstract: Microvascular endothelial cells play a pivotal role in the pathogenesis of sepsis-induced inflammatory responses and multiple organ failure. Therefore, they represent an important target for pharmacological intervention in the treatment of sepsis. Glucocorticosteroids were widely used in the treatment of sepsis but vast evidence to support their systemic use is lacking. The limited effects of glucocorticoids in the treatment of sepsis may be explained by differential effects of drug initiated NF-κB inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Based on above PLNs, we designed a positively charged drug delivery system (DDS) for glomerulus delivery. VCAM-1 is reported to be highly expressed on glomerular cell surface under inflammatory conditions [18,29,37,38]. Indeed, we confirmed that the expression of VCAM-1 did significantly increase on the surface of MRGEC (glomerular endothelial cell) and MPC5 (podocytes) cells after LPS treatment (which induces inflammation) (Figs.…”
Section: Fabrication and Optimization Of Plns And Pc-plnssupporting
confidence: 83%
See 1 more Smart Citation
“…Based on above PLNs, we designed a positively charged drug delivery system (DDS) for glomerulus delivery. VCAM-1 is reported to be highly expressed on glomerular cell surface under inflammatory conditions [18,29,37,38]. Indeed, we confirmed that the expression of VCAM-1 did significantly increase on the surface of MRGEC (glomerular endothelial cell) and MPC5 (podocytes) cells after LPS treatment (which induces inflammation) (Figs.…”
Section: Fabrication and Optimization Of Plns And Pc-plnssupporting
confidence: 83%
“…7). It was reported that TNF-α can upregulate VCAM-1 through the NF-κB pathway [30,[41][42][43], but CLT could act as an inhibitor of NF-κB [9,12,15,16,[36][37][38][39]. Hence, it is possible that CLT inhibit the expression of downstream VCAM-1 via downregulating both TNF-α and NF-κB pathway.…”
Section: Mechanic Study Of Clt On Nephritis Treatmentmentioning
confidence: 99%
“…In contrast, the key priorities in drug delivery pursued in our study include ratio of uptake in the target organ to that in other organs (e.g., brain to liver), the kinetics of drug delivery and postdelivery fate/activity of the pharmacological cargo (controlled by its release or/and interaction in the target), cellular and subcellular localization, the dose of drug delivered, and amplitude and duration of its effect. It might seem logical in retrospect that targeted drug delivery to VCAM-1-a selective yet scarce target-afforded no improvement in treatment of acute vascular inflammation in animal studies (63). Therefore, VCAM-1 targeted cerebrovascular pharmacological intervention documented in the present study represents the important outcome advancing the field of drug delivery to the brain.…”
Section: Discussionmentioning
confidence: 84%
“…Along these lines, the targeted delivery of antiinflammatory agents to the vasculature of affected sites via cell adhesion molecules represents a promising strategy (12)(13)(14). Using inflammation as the cue, a diverse range of nanodelivery systems have been designed to target upregulated markers such as VCAM1 and ICAM1 (15)(16)(17)(18)(19)(20), and this approach has been leveraged to treat conditions such as cancer and cardiovascular diseases (21)(22)(23). More recently, cell membrane coating technology has garnered considerable attention in the field of nanomedicine (24,25).…”
Section: Introductionmentioning
confidence: 99%